ELK1‐induced upregulation of lncRNA TRPM2‐AS promotes tumor progression in gastric cancer by regulating miR‐195/ HMGA1 axis. Issue 10 (19th May 2019) - Huang, Bo; Chang, Cheng; Wang, Bai‐lin; Li, Huiwen
Abstract: Long noncoding RNAs (lncRNAs) have been confirmed to be aberrantly expressed in various diseases including tumors. Recently, a new tumor‐related lncRNA, lncRNA TRPM2 antisense RNA (TRPM2‐AS), was shown to be involved in many tumors, such as lung cancer and breast cancer. However, the expression and role of TRPM2‐AS in the development of gastric cancer (GC) have not been elucidated. In the current study, we provided evidence that the expression levels of TRPM2‐AS were increased in both GC tissues and cell lines. We also showed that overexpression of TRPM2‐AS was modulated by ELK1, a transcription factor. The results of clinical assays showed that higher expressions of TRPM2‐AS were significantly related with invasion depth, TNM stage, lymphatic metastasis, and shorter overall survival. Further clinical assays using multivariate analysis suggested that TRPM2‐AS expression was an independent prognostic factor in patients with GC. Functional experiments illustrated that depression of TRPM2‐AS suppressed proliferation, migration, and invasion in GC cells. In terms of mechanism, we found that TRPM2‐AS directly inhibited miR‐195, which targeted the 3′‐untranslated region of high‐mobility group AT‐hook 1 (HMGA1) messenger RNA. Overall, these findings revealed that ELK1‐induced overexpression of TRPM2‐AS promoted the development and progression of GC in part through miR‐195/HMGA1 signaling axis, and established its candidacy as a new cancer biomarker for GC patients. Abstract : We first showed that ELK1‐induced upregulation of long noncoding RNA TRPM2‐AS promotes tumor progression in gastric cancer by regulating microRNA‐195/high‐mobility group AT‐hook 1 axis.